1988
DOI: 10.1002/aoc.590020406
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of arsenic trioxide in hamsters with liver damage induced by long‐term administration of carbon tetrachloride

Abstract: One-time oral administration of arsenic trioxide to hamsters with toxic liver cirrhosis induced by longterm exposure to carbon tetrachloride resulted in significant elevations of the concentrations of dimethylarsenic species in the liver and in blood, and in high urinary excretions of dimethylarsenic species. These concentration changes in the liver, blood and urine indicated that the methylation of inorganic arsenic was not inhibited but promoted in hamsters suffering from experimentally induced toxic liver c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Exposure of humans to either arsenates or arsenites results in increased levels of inorganic As(+3), inorganic As(+5), MMA, and DMA in urine (Aposhian et al 2000a(Aposhian et al , 2000bBuchet et al 1981aBuchet et al , 1981bConcha et al 1998aConcha et al , 1998bCrecelius 1977;Kurttio et al 1998 1985; Smith et al 1977;Tam et al 1979b;Vahter 1986). Similar results are obtained from studies in mice (Vahter 1981;Vahter and Envall 1983), hamsters (Hirata et al 1988;Marafante and Vahter 1987;Takahashi et al 1988), and rabbits (Maiorino and Aposhian 1985;Marafante et al 1985;Vahter and Marafante 1983). Historically, little distinction was made between MMA(V) and MMA(III) in the urine in most studies, and the assumption was that the majority of MMA in the urine was MMA(V); however, Aposhian et al (2000aAposhian et al ( , 2000b demonstrated that the methylated arsenic atom may be in either valance state.…”
Section: Metabolismsupporting
confidence: 61%
“…Exposure of humans to either arsenates or arsenites results in increased levels of inorganic As(+3), inorganic As(+5), MMA, and DMA in urine (Aposhian et al 2000a(Aposhian et al , 2000bBuchet et al 1981aBuchet et al , 1981bConcha et al 1998aConcha et al , 1998bCrecelius 1977;Kurttio et al 1998 1985; Smith et al 1977;Tam et al 1979b;Vahter 1986). Similar results are obtained from studies in mice (Vahter 1981;Vahter and Envall 1983), hamsters (Hirata et al 1988;Marafante and Vahter 1987;Takahashi et al 1988), and rabbits (Maiorino and Aposhian 1985;Marafante et al 1985;Vahter and Marafante 1983). Historically, little distinction was made between MMA(V) and MMA(III) in the urine in most studies, and the assumption was that the majority of MMA in the urine was MMA(V); however, Aposhian et al (2000aAposhian et al ( , 2000b demonstrated that the methylated arsenic atom may be in either valance state.…”
Section: Metabolismsupporting
confidence: 61%